Unocad, tecnologie per l'arte in sicurezza - Unocad, Unocad (Archeomatica, 2014)
The protective shells of UNO-CAD advanced technology for high-security transport of works of art are the result of a constant search for technological solutions to the diverse needs of the conservation of artistic heritage.